A Case for Facade Located Solar Thermal Collectors - MCCORMACK, SARAH (My University, 2015)
This paper explores the potential for façade located solar thermal collectors. Building typologies with limited roof space area are highlighted. A relationship exists between hot water consumption and the solar collector area; hence, a literature review of the hot water consumption of different building typologies is conducted. The review showed that there is a paucity of information on the hot water consumption of buildings, primarily attributed to the difficulty in quantifying it. The hot water consumption is typically describedusing liters per capita per day (Lcd) units, with a broad range of values existing, dependent, primarily on the building's function and location. Asimulation-based study is conducted to size solar thermal systems for different buildings and their associated hot water loads. High solar fractions,for buildings with high levels of hot water consumption, could only be achievedby using significantly largercollector surface areas. As a result, façade located solar thermal collectors are required for certain high-rise buildings that aim to provide for their hot water needs using a considerable portion of solar energy.
Keywords: Domestic hot water; Solar thermal; Solar fraction; Façade